2014
DOI: 10.1088/0964-1726/23/3/035021
|View full text |Cite
|
Sign up to set email alerts
|

Energy-harvesting linear MR damper: prototyping and testing

Abstract: The present study is concerned with an energy-harvesting linear MR (EH-LMR) damper which is able to recover energy from external excitations using an electromagnetic energy extractor, and to adjust itself to excitations by varying the damping characteristics. The device has three main components: an MR part having a damper piston assembly movable in relation to the damper cylinder under an external excitation, a power generator to produce electrical power according to the relative movement between the damper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 22 publications
0
40
0
Order By: Relevance
“…This study recalls two former papers by the author, see Sapiński (2011Sapiński ( , 2014. The first work demonstrated that the developed MR damper-based vibration control system with energy harvesting capability (comprising a commercially available linear MR damper and an electromagnetic power generator prototype) was able to power-supply the MR damper whilst the generator served as a "velocity-sign" sensor.…”
Section: Introductionmentioning
confidence: 71%
“…This study recalls two former papers by the author, see Sapiński (2011Sapiński ( , 2014. The first work demonstrated that the developed MR damper-based vibration control system with energy harvesting capability (comprising a commercially available linear MR damper and an electromagnetic power generator prototype) was able to power-supply the MR damper whilst the generator served as a "velocity-sign" sensor.…”
Section: Introductionmentioning
confidence: 71%
“…(Li et al, 2013a(Li et al, , 2013b presented an innovative concept of a mechanical motion rectifier which converts bidirectional motion into unidirectional motion. This paper deals with velocity sensing of the MRD prototype and recalls three former works of the author (Sapiński, 2011, 2014, Sapiński et al, 2016). The study is organized as follows.…”
Section: Introductionmentioning
confidence: 80%
“…Application of magnetorheological (MR) fluid‐based dampers have recently been reported for energy harvesting from vehicles' suspension systems . Chen and Liao proposed a self‐powered, self‐sensing MR damper that incorporated energy harvesting, dynamic sensing, and MR damping in a single unit.…”
Section: Technologies Of Energy Harvesting From Pavements and Roadwaysmentioning
confidence: 99%